A perspective review on impact and molecular mechanism of environmental carcinogens on human health. Issue 2 (3rd July 2021) - Malik, Sumira; Prasad, Shilpa; Kishore, Shristi; Kumar, Abhishek; Upadhyay, Vineet
ABSTRACT: Cancer is one of the leading causes of death all around the world. It is a group of diseases characterized by abnormal and uncontrollable division of cells leading to severe health conditions and fatality if remains undiagnosed till later stages. Cancer can be caused due to mutation or sudden alterations by effect of certain external agents. Agents that can cause sudden alterations in the genetic content of an individual are known as mutagens. Mutations can lead to permanent changes in the genetic constituency of an individual and possibly lead to cancer. Mutagenic agents that possess the capacity to induce cancer in humans are called carcinogens. Carcinogens may be naturally present in the environment or generated by anthropogenic activities. However, with the progress in molecular techniques, genetic and/or epigenetic mechanisms of carcinogenesis of a wide range of carcinogens have been elucidated. Present review aims to discuss different types of environmental carcinogens and their respective mechanisms responsible for inducing cancer in humans.